Against the Wind—Sustainability, Migration, Presidential Discretion - Ferrey, Steven (Columbia Journal of Environmental Law, 2019)
The weekend before Christmas 2018, the United States government began its longest shutdown in history, which extended well into the new year. The crisis was the result of the ongoing legal controversies surrounding migratory rights and U.S. immigration policy, and following the shutdown, President Trump declared a national emergency at the southern border. The executive branch has a constitutional responsibility to enforce all U.S. laws. However, while the Trump administration has focused pointedly on executive branch enforcement of immigration and migratory laws at the southern border, it has made no effort to enforce an international treaty and three long-standing U.S. statutes protecting migratory birds. More than one thousand species of birds are legally protected by U.S. law, making it a criminal felony, punishable by up to two years jail time and fines of up to one-quarter million dollars, for killing even a single migratory bird. Despite these harsh penalties, hundreds of thousands of these statutorily protected birds are killed by wind power turbines in the U.S. each year. Wind power, however, is an indispensable tool to address global climate change for a multitude of reasons. For instance, wind power is an essential technology to reduce U.S. greenhouse gas emissions and to meet the goals the U.S. previously pledged as part of the international Paris Agreement of 2016. Wind power does not emit either carbon-dioxide (“CO2”) or methane into the atmosphere, nor does it contribute to climate change. Further, wind power has been the leading source among all new electric power technologies installed in the U.S. for the past decade, and wind power is now cost-competitive with most other means of power generation. The U.S. Department of Homeland Security has also identified sixteen critical infrastructure sectors in the United States, each of which depends fundamentally on a stable power supply, a requirement that can be bolstered, if not achieved, by wind. Creating legal and economic implications for the power sector, the Trump administration announced its unilateral executive policy not to enforce the Migratory Bird Treaty Act (“MBTA”), a century-old statute that implements an eponymous treaty protecting migratory birds. The cessation of legal enforcement of the MBTA will decrease the costs of wind facilities, as the MBTA makes the killing of a single bird on any day a felony crime. There is now a yin and yang for wind power. Civil law is populated with important state and federal economic and legal incentives for wind power generation and infrastructure transition. Yet, federal investment tax incentives are currently being phased out and the newest tax regime is not nearly as supportive. In a parallel legal realm, criminal law creates an elevated risk for the decidedly modest number of wind turbines that kill an estimated one-quarter million protected birds annually in the U.S. There is a temporal mismatch between these federal criminal statutes, a transitory policy which does not enforce those laws, and civil law incentives for the industry. However, this criminal risk for wind facilities is not static; it changes with different occupants of the executive branch which enforces federal criminal law. There is an added dimension when the technology involved is not a mere substitute commodity, but is critical to mitigate global climate change. This confluence of competing factors requires reconciliation by legislative change, regulatory clarification, or judicial determination. This Article navigates several layers of this emerging technology- species conflict and its counterposed statutory objectives to chart a new direction in U.S. law.